DNA Methylation Manipulation of Memory Genes Is Involved in Sevoflurane Induced Cognitive Impairments in Aged Rats - Ni, Cheng; Qian, Min; Geng, Jiao; Qu, Yinyin; Tian, Yi; Yang, Ning; Li, Shuai; Zheng, Hui (Frontiers in Aging Neuroscience, 2020)
DNA methylation is an essential epigenetic mechanism involving in gene transcription modulation. An age-related increase in promoter methylation has been observed for neuronal activity and memory genes, and participates in neurological disorders. However, the position and precise mechanism of DNA methylation for memory gene modulation in anesthesia related cognitive impairment remained to be determined. Here, we studied the effects of sevoflurane anesthesia on the transcription of memory genes in the aged rat hippocampus. Then, we investigated changes in DNA methylation of involved genes and verified whether dysregulated DNA methylation would contribute to anesthesia induced cognitive impairment. The results indicated that sevoflurane anesthesia down-regulated the mRNA and protein levels of three memory genes, Arc, Bdnf, and Reln, which were accompanied with promoter hypermethylation and increased Dnmt1, Dnmt3a, and Mecp2 expression, and finally impaired hippocampus dependent memory. Furthermore, inhibition of DNA hypermethylation by 5-Aza rescued sevoflurane induced memory gene expression decrease and cognitive impairment. These findings provide an epigenetic understanding for the pathophysiology of cognitive impairment induced by general anesthesia in aged brain.